Provision of disabled facilities at the Malaysian electrical train service (ets) station towards social sustainability / Nur Ainaa Azmi, Haryati Mohd Isa and Siti Rashidah Md Sakip - Azmi, Nur Ainaa; Mohd Isa, Haryati; Md Sakip, Siti Rashidah (2019)
Sustainable design for transportation system is important especially for social sustainable of people with disabilities (PWDs). The stations must provide user-friendly facilities for everyone. Although the facilities were provided, but some of them do not function properly and cannot be used by PWDs. The facilities for PWDs must fulfilled with the Malaysian Standards (MS). The research aim at determining the compliance of facilities for PWDs to be provided at ETS stations. Two research objectives were established (1) to identify the range of facilities for PWDs at the ETS station and (2) to investigate the compliance of facilities for PWDs to be provided at ETS stations with the MS. Two ETS stations that build in 2014 and above were chosen for the case study. Purely qualitative methods were adopted. An observation checklist was created based on the MS to see the availability and compliance of the facilities. The findings suggest that there are 10 main facilities for PWDs to be provided at ETS stations. Most of the facilities are available and comply with the MS. Otherwise, the primary way to enhance the social sustainability among PWDs is to provide and improve the facilities for PWDs at ETS stations.